Value of PI of uterine artery at 23-24 weeks in the prediction of adverse pregnancy outcome - Dhar, Anshu; Kaul, Indu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Increased resistance in uteroplacental circulation is associated with pregnancy complications. The aim of this study was to determine the role of uterine artery PI at 23-24 weeks gestation in predicting adverse pregnancy outcomes. Methods: 200 singleton pregnancies were prospectively examined with color Doppler to determine the PI of uterine artery at 23-24 weeks and study its correlation with subsequent development of adverse maternal and fetal outcomes defined as any or the combination of preeclampsia, intrauterine growth restriction (IUGR), intrauterine death (IUD), preterm delivery and placental abruption. Results: There were 13 cases (6.5%) with abnormal uterine artery Doppler results and 8 (61.5%) of them developed preeclampsia, out of these 8, 1 had IUGR as well and 3 had iatrogenic preterm delivery due to severe preeclampsia. 2 (15.4%) out of 13 had only IUGR. The pregnancies with adverse outcomes had significantly higher mean PI than those with normal outcomes (1.2±0.3 versus 0.857±0.179; p <0.001). The sensitivity, specificity, PPV and NPV of PI ≥95th percentile in the prediction of adverse pregnancy outcome was 35.71%, 98.26%, 76.92% and 90.37% respectively. The birth weight in higher mean PI group was significantly lower than in pregnancies with PI <95th percentile (2.33±0.49 kg versus 2.86±0.48 kg; p <001). No cases of spontaneous preterm labor, IUD or abruption were present in higher mean PI group. Conclusions: Increased uterine artery PI at 23-24 weeks of pregnancy is associated with an increased risk of adverse pregnancy outcomes.